Available Surfaces : Essays on Poesis - Hummer, T. R. (Book collections on Project MUSE., 2012)
"T. R. Hummer grew up in the Deep South and planned to become a musician before he met poetry. This musical influence is visible in his work: he often discusses poetry together with music (and sometimes the other way around), and his career has included both writing and performance. The present volume, Available Surfaces, focuses on the art of making both poetry and music and on the concept of "making" as well. Hummer draws on childhood experiences ("A Length of Hemp Rope"), adult experiences ("Hotel California"), experiences as a poet ("Available Surfaces"), and experiences as an explorer of unworldly spaces ("The Hive," "Brain Wave and the End of Science Fiction"). Hummer has published ten volumes of poetry with presses including Louisiana State University Press and the University of Illinois Press. His work has appeared in two anthology volumes published by Simon & Schuster and Cengage and in two Pushcart Prize anthologies. He has edited the Kenyon Review, the Georgia Review, and the Cimarron Review, among other journals."--